"I Feel A Lot Better About It": Professional Identity Development in the Context of a Film-Based Assignment. Issue 2 (3rd April 2021) - Olson, Joann S.; Autry, Linda; Moe, Jeffry
ABSTRACT: Developing a professional identity as a counselor is a key element of counselor training. Because of the complexity of this identity, the counselor trainee needs to acquire, internalize, and integrate skills and knowledge from multiple theories, experiences, and sources. This article describes how a film-based assignment given to students in a group counseling class promoted the development of participants' professional identity. In addition, those students' later reflections on the assignment and the class demonstrate the complexity and ongoing nature of that identity development. The findings of this study suggest that creative approaches to assignments may contribute to broader and longer-term learning objectives of the training program as a whole, above and beyond providing assessment of a particular course objective.